Heterosis studies for quantitative traits in interspecific hybrids of cotton (Gossypium hirsutum L. Ã— Gossypium barbadense L.) - Adsare, Anil Devidas; Salve, Abhay Narayan; Patil, Narendrakumar Prakash (Journal of Phytology, 2017)
A study was conducted in interspecific cotton hybrids (Gossypium hirsutum L. Ã— Gossypium barbadense L.) to assess the extent of the heterosis for eight yield and yield attributing traits. Twelve lines of G. hirsutum and five testers of G. barbadense were crossed in line x tester manner to develop 60 F1 hybrids. Analysis of variance revealed the significant differences among the crosses for all traits. Heterosis was worked out over mid parent, better parent and two standard checks i.e. MRC 7918 and Varalaxmi. Crosses RAH1065 x SUJALA, PH1075 x SUJALA, PH348 x SUJALA and DHY286 x Suvin were the best heterotic combinations for seed cotton yield and could be utilized for hybrid development. These hybrids were shown desirable heterosis for seed cotton yield along with other yield components. These hybrids may be tested in large scale trial to confirm the superiority in heterosis.